2017
DOI: 10.1016/j.neuropharm.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pharmacotherapies for alcohol use disorder

Abstract: The identification of different stages within the alcohol use disorder (AUD) cycle that are linked to neurocircuitry changes in pathophysiology associated with the negative emotional states of abstinence has provided a view of medication development for AUD that emphasizes changes in the brain reward and stress systems. Alcohol use disorder can be defined as a chronic relapsing disorder that involves compulsive alcohol seeking and taking, loss of control over alcohol intake, and emergence of a negative emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 142 publications
(150 reference statements)
0
31
0
2
Order By: Relevance
“…There are several recent reviews from 2016-2018 providing the details of other important stress responsive systems (like Corticotrophin Releasing Factor, Neuropeptide Y, and glucocorticoid receptor, etc.) from preclinical evidence to the recent clinical trials [Koob and Mason, 2016;Mantsch et al, 2016;Blaine and Sinha, 2017;Mason, 2017;Robinson and Thiele, 2017;Spierling and Zorrilla, 2017;Tunstall et al, 2017;Pomrenze et al, 2017]. The main focus in this mini-review is several other important stress responsive systems, which recently has not been reviewed, like arginine vasopressin/V1b receptors (Part I), and proopiomelanocortin/β-endorphin (Part II).…”
Section: Introductionmentioning
confidence: 99%
“…There are several recent reviews from 2016-2018 providing the details of other important stress responsive systems (like Corticotrophin Releasing Factor, Neuropeptide Y, and glucocorticoid receptor, etc.) from preclinical evidence to the recent clinical trials [Koob and Mason, 2016;Mantsch et al, 2016;Blaine and Sinha, 2017;Mason, 2017;Robinson and Thiele, 2017;Spierling and Zorrilla, 2017;Tunstall et al, 2017;Pomrenze et al, 2017]. The main focus in this mini-review is several other important stress responsive systems, which recently has not been reviewed, like arginine vasopressin/V1b receptors (Part I), and proopiomelanocortin/β-endorphin (Part II).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies and early phase clinical trials have focused on a wide variety of potential new treatments for AUD such as targeting neuropeptide, opioid, cannabinoid, nicotinic, dopaminergic, glycinergic, GABAergic and glutamatergic receptors. A few possible new treatments for AUD based on recent research include gabapentin, topiramate, baclofen and varenicline (4,54). The most relevant neurotransmitter systems and thus the appropriate treatment will likely be based on individual differences between patients as well as the target phase of the addiction cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal/negative affect models include hangover anxiety and increased motivation to obtain alcohol in a dependent state that can be induced by alcohol vapor exposure or prolonged IA to alcohol. Finally, anticipation/preoccupation/craving models includes cue-and stress-induced reinstatement of alcohol-seeking behavior (37,54). Research and animal models focusing on these three key stages of AUD has been used to screen several promising targets for possible new treatments for AUD (Figure 3).…”
Section: Animal Models Of Alcohol Use Disordermentioning
confidence: 99%
“…Based on several clinical studies, it can be confirmed that prolonged alcohol use, genetic factors, psychosocial, cognitive, and environmental risk factors could play a role in the individual variability in the development of moderate to severe AUD [4,[6][7][8]. Understanding the mechanisms that underlie individual vulnerability to moderate to severe AUD may help enhance the number of effective treatment strategies for AUD and reduce the economic burden associated with the disorder [9,10].…”
Section: Introductionmentioning
confidence: 99%